The effect of low-volume preseason plyometric training on force-velocity profiles in semiprofessional Rugby Union players - Watkins, C. M.; Gill, N. D.; Maunder, E.; Downes, P.; Young, J. D.; McGuigan, M. R.; Storey, A. G. (The Journal of Strength and Conditioning Research, 2021)
Rugby union is a physically demanding and complex team sport requiring athletes across all positions to express speed and acceleration. Plyometrics can effectively improve speed profiles by enhancing both force- and velocity-(FV) characteristics; however, the optimal dose and exercise direction for trained athletes is still relatively unknown. Therefore, the aim of this investigation was to determine the efficacy of a low-dose, directionally specific plyometric training program for improving speed profiles in semiprofessional rugby players. Players were randomly allocated to one of 2 plyometric training groups that performed low-volume (40-60 ground contacts per session) plyometrics twice weekly, or a control group that did not participate in any plyometric training. The 2 training groups underwent reverse back-to-back three-week vertically and horizontally focused plyometric training programs, with a 12-day washout. Body composition, aerobic capacity, and sprint performance (10-, 20-, 30-m split time, horizontal FV profile) were measured. During the intervention, HV-1 (horizontal/vertical training group 1) improved sprint performance (n = 12; Delta 30 m = -0.020 seconds; p = 0.038), VH-2 (vertical/horizontal training group 2) maintained sprint performance (n = 8; Delta 30 m = +0.049 seconds; p = 0.377), and the control group progressively declined in sprint performance (n = 12; Delta 30 m = +0.071; p = 0.019). In addition, vertical plyometrics may preferentially benefit secondary acceleration (Delta 10-20 m split time: -0.01 seconds; p = 0.03) and many force-oriented FV profile characteristics. Correlational analyses (r2 = -0.568 to 0.515) showed sprint improvements were hindered in athletes with lower initial aerobic fitness, suggesting accumulated fatigue may have limited the magnitude of adaptation. Therefore, including low-volume plyometric training may be beneficial for improving sprint profiles or attenuating decrements realized during periods of high-volume sport-specific training.